The Impact of Strategic Planning on Key Performance Indicators in the Saudi Private Sector in Light of Saudi Vision 2030 - Alawwad, Arwa Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study examines the correlation between strategic planning and organizational performance, focusing on its impact across various dimensions such as economic factors, goal achievement, and customer satisfaction. Vision 2030 serves as a reference case for the study. In addition, the research investigates the distinctions in applying performance measurement to employees and the organization's strategic plan, while affirming the relationship between the study's variables. To achieve this, a tailored questionnaire was administered to employees in both governmental and private organizations, specifically those in strategic management and human resources departments. Furthermore, the study advocates for operational excellence to enable more astute business management, emphasizing the importance of innovation and adaptability in enhancing reputation, loyalty, and brand value.
Keywords: Vision 2030; strategic planning; businesses objectives; organizations; Key Performance Indicators (KPIs)